Assessing Urban Community Gardens' Impact on Net Primary Production using NDVI. Issue 1 (25th May 2017) - Parece, Tammy E.; Campbell, James B.
Abstract : Community gardens are one form of urban agriculture–growing of food and non‐food products for sale or consumption within urban and peri‐urban areas. Urban community gardens provide many benefits, including provisioning of fresh and nutritious foods, supporting environmental education, nurturing social interaction and community building, and contributing to sustainability. In many cities worldwide, urban agriculture is now integrated within urban planning programs. Although social, community, and nutritional benefits of community gardens are well documented, few quantitative assessments of their environmental benefits exist. None have applied Normalized Difference Vegetation Index (NDVI) as an environmental metric. NDVI is widely used in forestry and agriculture to track changes in vegetation phenology, assess vegetation stress and health, and, in urban areas, to separate vegetation from impervious surfaces. NDVI has a positive relationship with net primary production. We used NDVI product from U.S. satellites–Landsats 5, 7, and 8–to assess urban community garden sites. We conducted a time series analysis over the 2007 to 2015 growing seasons (May–September) for three eastern U.S. cities–Roanoke, VA; Pittsburgh, PA; and Buffalo, NY. Our results show that establishment of community gardens alter seasonal NDVI trajectories, sometimes with initial declines, but then increasing over time. Furthermore, NDVI profiles reveal the vigorous character of urban agriculture.